2010
DOI: 10.4314/ajpsy.v13i4.61881
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effectiveness of existing psycho-educational material (The Alliance Programme) for patients suffering from schizophrenia in the South African context

Abstract: Objective: The objective of this study was to test the effectiveness of the existing psycho-educational material (The Alliance Programme) for patients suffering from schizophrenia in the South African context. Method: A qualitative research approach was used. Fifteen Setswana speaking participants, with a diagnosis of schizophrenia were exposed to the programme. Semi-structured and screening interviews were used to collect demographic and clinical data. The participants were divided into two groups and were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
11
0
2
Order By: Relevance
“…; Pooe et al. ) and the use of community‐based rehabilitation methods (Asher et al. ; de Menil et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…; Pooe et al. ) and the use of community‐based rehabilitation methods (Asher et al. ; de Menil et al.…”
Section: Resultsmentioning
confidence: 99%
“…Pooe et al. () evaluated the effectiveness of psycho‐educational material for people living with schizophrenia in South Africa and found that the type of psycho‐education influenced the way some participants understood mental disorders. Asmal et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations